Folic acid and methotrexate use and their association with COVID-19 diagnosis and mortality: a case–control analysis from the UK Biobank. Issue 8 (24th August 2022) - Topless, Ruth; Green, Ralph; Morgan, Sarah L; Robinson, Philip; Merriman, Tony; Gaffo, Angelo L
Abstract : Objective: To determine if methotrexate or folic acid prescription was associated with differential risk for COVID-19 diagnosis or mortality. Design: Case–control analysis. Setting: The population-based UK Biobank (UKBB) cohort. Participants: Data from 380 380 UKBB participants with general practice prescription data for 2019–2021. Updated medical information was retrieved on 13 December 2021. Primary and secondary outcome measures: The outcomes of COVID-19 diagnosis and COVID-19-related mortality were analysed by multivariable logistic regression. Exposures evaluated were prescription of folic acid and/or methotrexate. Criteria for COVID-19 diagnosis were (1) a positive SARS-CoV-2 test or (2) ICD-10 code for confirmed COVID-19 (U07.1) or probable COVID-19 (U07.2) in hospital records, or death records. By these criteria, 26 003 individuals were identified with COVID-19 of whom 820 were known to have died from COVID-19. Logistic regression statistical models were adjusted for age sex, ethnicity, Townsend deprivation index, body mass index, smoking status, presence of rheumatoid arthritis, sickle cell disease, use of anticonvulsants, statins and iron supplements. Results: Compared with people prescribed neither folic acid nor methotrexate, people prescribed folic acid supplementation had increased risk of diagnosis of COVID-19 (OR 1.51 (1.42–1.61)). The prescription of methotrexate with or without folic acid was not associated with COVID-19 diagnosis (p≥0.18). People prescribed folic acid supplementation had positive association with death after a diagnosis of COVID-19 (OR 2.64 (2.15–3.24)) in a fully adjusted model. The prescription of methotrexate in combination with folic acid was not associated with an increased risk for COVID-19-related death (1.07 (0.57–1.98)). Conclusions: We report an association of increased risk for COVID-19 diagnosis and COVID-19-related death in people prescribed folic acid supplementation. Our results also suggest that methotrexate might attenuate these associations.